The Effect of Temperature and Heating Time to Antioxidant Activity of Onion Dayak Bulb Extract (Eleutherine palmifolia): Antioxidant Activity of Onion Dayak Bulb Extract (Eleutherine palmifolia) - Mutiara, Roza; Ulyarti, Ulyarti; Yulia, Ade (Jurnal Bio-Geo Material Dan Energi, 2023)
Onion Dayak (Eleutherine palmifolia) is a typical plant of center Kalimantan which has been used hereditary as medicine by Dayak people. The part of this plant that is used as medicine is the bulb. Empirically, the bulb of onion Dayak can heal diabetic disease, hypertension, cancer and lower cholesterol level. The aimed of this study is to know the effect of heating temperature and heating time to the antioxidant activity of onion Dayak bulb extract (Eleutherine palmifolia). This study was using a completely randomized design (CRD) with factorial pattern. Two factor used in this study were heating temperature (75, 85, 95 ºC) and heating time (5, 10, 15 minutes). This study was performed in three replications. The result showed that heating temperature and heating time has a significance effect on the yield, antioxidant activity value and IC50. The treatment of 75ºC for 5 minutes of heating was the best combination of heating temperature and heating time with the value yield (76,50%), antioxidant activity value (63,72%), IC50 (33,05µg/ml), color: L* 43,25, a*-2,01, b* 18,4. Phytochemical analysis showed that the extract of onion Dayak bulb contains phenolic and flavonoid compounds.